2021
DOI: 10.1002/admi.202101619
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Structural and Flexible Reduced Graphene Oxide/Ti3C2Tx Composite Film Electrode with Long Cycle Life for Supercapacitor

Abstract: Poor rate capability due to the sheet self‐stacking of conventional MXene electrode limits their electrochemical application to some extent. Herein, incorporating reduced graphene oxide into Ti3C2Tx MXene is reported to improve the electrochemical performance, cycle lifetime, and mechanical flexibility significantly. Graphene oxide is reduced by thermal heating, by which it can release gas locally to induce micro‐surface structure. The resulting film with an introduction of 20 wt% graphene oxide exhibits an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The appearance of the (002) plane characteristic peak of γ-rGO at 24° proves the efficient reduction of γ-irradiation. , Compared with the multiple sharp characteristic peaks of MAX (JCPDS: 29–0101), V 2 C retained the (002) plane characteristic peak located at 2θ = 7.4°, indicating the successful etching and delamination of MXene. , The corresponding characteristic peaks of γ-rGO in GMF after adding V 2 C still exist, indicating that γ-rGO is the main framework in GMF. Similar to V 2 C, GMF also exhibits a (002) peak at 2θ = 7.4°, indicating an interlayer spacing of 1.71 nm, which is consistent with that seen by AFM. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the (002) plane characteristic peak of γ-rGO at 24° proves the efficient reduction of γ-irradiation. , Compared with the multiple sharp characteristic peaks of MAX (JCPDS: 29–0101), V 2 C retained the (002) plane characteristic peak located at 2θ = 7.4°, indicating the successful etching and delamination of MXene. , The corresponding characteristic peaks of γ-rGO in GMF after adding V 2 C still exist, indicating that γ-rGO is the main framework in GMF. Similar to V 2 C, GMF also exhibits a (002) peak at 2θ = 7.4°, indicating an interlayer spacing of 1.71 nm, which is consistent with that seen by AFM. , …”
Section: Resultsmentioning
confidence: 99%
“…Similar to V 2 C, GMF also exhibits a (002) peak at 2θ = 7.4°, indicating an interlayer spacing of 1.71 nm, which is consistent with that seen by AFM. 25,43 The XPS test further illustrates the elemental composition of V, C, and O and the chemical bonding states in GMF (Figure S4). The high-resolution C 1s spectra of GMF can be deconvoluted into five components (Figure 1g 23,44 The V 2p level spectrum of GMF could be deconvoluted into three doublets, which are attributed to V−C/V 4+ (517.2 eV), V 3+ (514.5 eV), and V−O/V 2+ (513.7 and 521.3 eV) (Figure 1h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the high‐resolution spectum of C 1s ( Figure a), four components centered at 281.7, 284.6, 285.1, and 288.9 eV can be assigned to CTi, CC, CO, and OCO bonds, respectively. [ 8 ] For Ti 2p spectrum (Figure 4b), three doublets (Ti 2p 3/2 Ti 2p 1/2 ), which are fitted at 455.0, 456.2, 458.9, 460.7, 461.9, and 464.4 eV, can be assigned to TiC 2p 3/2 , TiX 2p 3/2 , TiO 2p 3/2 , TiC 2p 1/2 , TiX 2p 1/2 , and TiO 2p 1/2 bonds, respectively. [ 40,41 ] For Fe 2p spectrum (Figure 4c), showing two main peaks at 710.9 and 724.5 eV and two satellite peaks at 715.8 and 729.4 eV, which can be assigned to Fe 3+ characteristic peaks in hematite.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] However, 2D MXene nanoflakes usually suffer from serious re-stacking due to the intense van der Waals force, which reduces the effective active sites and ion transport channels. [8] In order to avoid this tendency and improve the electrochemical performance of film electrodes, a series of interesting strategies has been reported and carried out. For example, introducing the second phase among the interlayer of MXene, such as noble metal nanoparticle (Au, Ag, Pt, etc.…”
mentioning
confidence: 99%
“…The low-rate performance caused by the sheet self-stacking of the traditional MXene electrode limits its electrochemical application to a certain extent. Luo et al [ 95 ] reported the preparation of a reduced graphene oxide/Ti 3 C 2 T x electrode for a supercapacitor. The fabricated composite electrode exhibited outstanding electrochemical performance and mechanical flexibility, and still maintained excellent cycle stability after 32,000 charge-discharge cycles.…”
Section: Applications Of Mxene-based Heterostructuresmentioning
confidence: 99%